2012
DOI: 10.1002/acr.21629
|View full text |Cite
|
Sign up to set email alerts
|

Multiple joint involvement in total knee replacement for osteoarthritis: Effects on patient‐reported outcomes

Abstract: Objective. To determine whether symptomatic (painful/problematic) joints pre-total knee replacement (TKR) surgery influence 1) pre-and 12-month post-TKR patient-reported outcomes (pain, physical function, and mood [fatigue, anxiety, and depression]) and 2) postsurgical pain and function mediated through mood. Methods. A total of 494 participants completed the patient-reported outcome measures pre-and 12-months post-TKR. Symptomatic (painful/problematic) joints affected by arthritis were indicated on a homuncul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 37 publications
3
78
0
Order By: Relevance
“…However, other studies have suggested depressive symptoms have little influence on pain or function postoperatively [21,25]. Our study was hypothesis-driven because several studies have reported inconsistent findings related to the prognostic value of preoperative depressive symptoms and the extent to which depressive symptoms change from the pre-to the postoperative period [5,6,12,16,17]. We found that preoperative depressive symptoms were not prognostic of the extent of postoperative pain and that the extent of depressive symptoms was essentially unchanged after surgery.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…However, other studies have suggested depressive symptoms have little influence on pain or function postoperatively [21,25]. Our study was hypothesis-driven because several studies have reported inconsistent findings related to the prognostic value of preoperative depressive symptoms and the extent to which depressive symptoms change from the pre-to the postoperative period [5,6,12,16,17]. We found that preoperative depressive symptoms were not prognostic of the extent of postoperative pain and that the extent of depressive symptoms was essentially unchanged after surgery.…”
Section: Discussionmentioning
confidence: 62%
“…Our study had limitations, and our findings cannot be directly compared with other studies [5,6,17,27] for a variety of reasons. Our data were collected from OAI, a natural history knee OA study unlike other studies examining the prognostic importance of postoperative Fig.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…A similar physician‐reported measure of joint‐specific previous surgical history was also included in the set. Physicians are asked to report these measures for all 4 joints, as multiple joint involvement affects outcomes 42.…”
Section: Resultsmentioning
confidence: 99%